What Is the Success of Implants Placed in Fibula Flap? A Systematic Review and Meta-Analysis - Pooja Gangwani; Mohammed Almana; Basir Barmak; Antonia Kolokythas (Stilus Optimus, 2022)
Objectives: The purpose of this systematic review and meta-analysis is to examine the success rate of osseointegrated dental implants placed secondarily in fibula free flaps using the Albrektsson and colleagues criteria. Material and Methods: A computerized database search was performed using PubMed, Embase, Web of Science and Cochrane CENTRAL. Specific ascertainment criteria were applied for the inclusion of the eligible studies. This systematic review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-analysis PRISMA checklist. Risk of bias was assessed for all the included studies. Results: The meta-analysis was carried using ten studies that met the inclusion criteria. The present review pooled data obtained from 242 patients (167 males and 75 females), with the age range of 13 to 79 years. A total of 848 dental implants were placed in the free fibula flaps. All dental implants were placed in a delayed fashion, ranging from 14 to 192 months. The estimated proportion of successful implants placed in fibula flaps used to reconstruct the maxillomandibular complex was 0.94 or 94% (95% CI [confidence interval] = 0.91 to 0.96]) with an insignificant heterogeneity of 37%, P = 0.12. Using a random effect model the annual implant failure rate was 0.02 with a 95% CI = 0.01 to 0.03. Conclusions: The results of this systematic review and meta-analysis strongly indicate that using objective criteria, delayed implant placement in free fibula flaps is highly successful.